2010
DOI: 10.3346/jkms.2010.25.7.1090
|View full text |Cite
|
Sign up to set email alerts
|

Falciform Ligament Abscess after Omphalitis: Report of a Case

Abstract: A falciform ligament abscess is a rare type of intra-abdominal abscess. A 2-yr-old male, who had omphalitis two months previously, presented with a fever and right upper quadrant abdominal pain. The ultrasound and CT scan showed an abdominal wall abscess located anterior to the liver, which was refractory to conservative management with percutaneous draninage and antibiotics. On the third recurrence, surgical exploration was performed and revealed an abscess arising from the falciform ligament; the falciform l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…It has been observed that infection can extend from liver, gallbladder or umbilicus to the falciform ligament. [2][3][4][5][6] Though in this case it was found that gallbladder was not acutely inflamed and no infective lesion was present in the abdominal cavity. Here, relationship with chronic cholecystitis could not be established.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It has been observed that infection can extend from liver, gallbladder or umbilicus to the falciform ligament. [2][3][4][5][6] Though in this case it was found that gallbladder was not acutely inflamed and no infective lesion was present in the abdominal cavity. Here, relationship with chronic cholecystitis could not be established.…”
Section: Discussionmentioning
confidence: 55%
“…After two months there was a recurrence of the abscess of falciform ligament secondary to acute calculous cholecystitis. 2 Other few cases of this condition have been reported in the setting of rupture of the gangrenous gallbladder, 3 portal pyemias, 4,5 post omphalitis, 6,7 post pancreatitis, 8 and infected ventriculoperitoneal shunt. 9 There is one case of an isolated falciform ligament necrosis presenting as acute abdomen has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, preoperative CT findings were confirmed intraoperatively. These findings included falciform ligament abscess [4], desmoid tumor appended to the round ligament [5], and infiltration of the round ligament [6].…”
Section: Discussionmentioning
confidence: 99%
“…This venous network might explain the mechanism of spread of infection from omphalitis into the falciform ligament in the absence of a round ligament (post-operative cases). 7 The cholecystic veins drain directly into the portal vein and the pericholedochal venous system. It is likely that the infection spreads from the biliary tree via the paraumbilical veins to the falciform ligament, leading to abscess formation.…”
Section: Discussionmentioning
confidence: 99%